CANDİDA’LARIN PATOJENLİK BELİRTGENLERİ - YÜCEL, Ayhan; KANTARCIOĞLU, A. Serda (Cerrahpaşa Medical Journal, 2014)
Background.- A number of factors mainly related to fungus species and strains have contributed to overcome the host defences. The so called pathogenicity determinants confer virulence on Candida albicans and otherCandida species. These factors are adherence (adhesion to mucosal surfaces), dimorphism (production of hyphae and resistance to phagocytosis), toxin and enzyme production and cell surface composition.